2007
DOI: 10.1126/science.1138050
|View full text |Cite
|
Sign up to set email alerts
|

Redirection of Silencing Targets by Adenosine-to-Inosine Editing of miRNAs

Abstract: Primary transcripts of certain microRNA (miRNA) genes are subject to RNA editing that converts adenosine to inosine. However, the importance of miRNA editing remains largely undetermined. Here we report that tissue-specific adenosine-to-inosine editing of miR-376 cluster transcripts leads to predominant expression of edited miR-376 isoform RNAs. One highly edited site is positioned in the middle of the 5′-proximal half "seed" region critical for the hybridization of miRNAs to targets. We provide evidence that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
739
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 726 publications
(785 citation statements)
references
References 19 publications
28
739
1
1
Order By: Relevance
“…In addition to editing in the miR-376 cluster described previously (Kawahara et al 2007b(Kawahara et al , 2008, we found another eight miRNAs that are edited within the seed of either the miRNA or the miRNA*. A-to-I editing could also affect miRNA loading, and thereby indirectly affect targeting.…”
Section: Rna Editingmentioning
confidence: 91%
“…In addition to editing in the miR-376 cluster described previously (Kawahara et al 2007b(Kawahara et al , 2008, we found another eight miRNAs that are edited within the seed of either the miRNA or the miRNA*. A-to-I editing could also affect miRNA loading, and thereby indirectly affect targeting.…”
Section: Rna Editingmentioning
confidence: 91%
“…In addition to recoding, a few beneficial ADAR targets in noncoding RNA are fixed (Fig. 2C), such as miRNA (47). Third, these fixed ADAR targets will also be lost via mutation.…”
Section: Random Selection and Fixation Model For The Emergence Of Novmentioning
confidence: 99%
“…Editing of microRNA precursors inhibits or alters processing and changes the sequence of both seed sequence in microRNAs and targeting sequences in mRNAs. [6][7][8]49 Transcribed primiRNAs are cleaved by Drosha, the resulting pre-miRNAs are exported from the nucleus to the cytoplasm and finally, the 21-23 bp miRNAs are generated by Dicer cleavage. One strand of the mature miRNA is incorporated into RISC (RNA-induced silencing complex) and binds to complementary sequences mainly in the 3' UTR of target mRNAs.…”
Section: Targets For Adenosine To Inosine Editingmentioning
confidence: 99%
“…Editing can affect their processing by Drosha or Dicer but can also alter microRNA:mRNA interactions. [5][6][7][8][9] In coding regions of mRNA editing events are relatively rare. However, during the last years several evolutionary conserved adenosine to inosine editing events have been identified in coding regions.…”
Section: Introductionmentioning
confidence: 99%